Kinematic and Singularity Analysis of PRoM-120 – A Parallel Robotic Manipulator with 2-PRU/PRS Kinematic Chains - Adriyan, Adriyan; Sufiyanto, Sufiyanto (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2018)
PRoM-120 was a parallel robotic manipulator which constructed by 2-PRU/PRS kinematic chains. The mobility of this manipulator was 3 DOF, i.e. 1 translational DOF, and 2 rotational DOF (1T2R). The objective of this research was to analyze kinematic, and singularity of PRoM-120 based on its geometrical configuration. Inverse kinematics and velocity analysis were carried out by applying loop vector equation. Meanwhile, all screw systems existed in PRoM-120 were derived using screw theory. Singularity analysis revealed that PRoM-120 had no constraint singularity within its workspace. The kinematic singularity of PRoM-120 showed similar condition to transmission singularity. Three types of both singularities were examined and presented for general condition and selected numerical value of kinematic constants having by PRoM-120. The selected numerical values of those kinematic constants showed only one pose for the singular condition, which was the direct kinematic or the output transmission singularity.